Antinociceptive effects of the combined use of butorphanol and buprenorphine in mice - Kazumasu Sasaki; Tatsuya Ishikawa; Kazutaka Ikeda; Shinya Kasai (Wiley, 2021)
Abstract Butorphanol and buprenorphine are mixed opioid receptor agonist‐antagonist drugs widely used as analgesics in people and animals. There are few reports concerning the interaction of multiple opioids, and their antinociceptive effects, when combined with other opioids, remain unclear. Therefore, we report the preliminary findings of the antinociceptive effects of the combined use of butorphanol and buprenorphine in C57BL/6JJcl mice. Both drugs were administered either simultaneously or in different orders. Compared with the baseline values, the tail‐flick and hot‐plate test latencies increased regardless of the order of administration. Furthermore, enhanced latencies were observed on administration of butorphanol followed by buprenorphine. Combined use of these drugs may not attenuate analgesic efficacy. Besides, enhancement of these effects can be obtained by changing the order of the administration of these drugs. It is necessary to further investigate the molecular basis of the underlying mechanism in future definitive studies.